Investigando o campo magnético das estrelas análogas e gêmeas solares através da espectropolarimetria - Duarte, Tharcisyo Sa e Sousa (2012)
This study proposes an observing program focused on the investigation of the stellar magnetism and dynamo evolution in cool active solar-like stars. More mainly in the solar analogs and twins. Observations of stars of our base were carried out with two spectropolarimeter (ESPaDOnS@CFHT and NARVAL@TBL). The analyse of stars in stage different allows an understanding of the dependence of magnetic activity on basic stellar parameters such as rotation, mass, age and depth of the convection zone. This study provides measures necessary for testing dynamo theories. The 65 targets for this project are solar type stars with mass spanning from 0:9 M=Mfi 1:075 solar masses and at different evolutionary stages. Our two main science objectives were, (i) To determine how the magnetic field evolved from the ZAMS to the TO (turn off) for stars with 0:9 M=Mfi 1:075; (ii) To determine the impact of convective depth and rotation on magnetic of cool stars of solar type. The main result from this study was the characterization of the dependence of magnetic field intensity as function of age, Rossby number and the convective zone deepening. This context, the availability of ESPaDOnS and NARVAL opens an exceptional possibility to study the magnetic properties of Sun-like stars by means of spectropolarimetric observations